2013
DOI: 10.1007/s40299-013-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Support for Innovation on Organizational Innovation: Taking Organizational Learning as a Mediator

Abstract: The purpose of this study was to examine the role of organizational learning as a mediator variable between support for innovation and organizational innovation. Samples for this study were randomly selected from 22 technological colleges in Taiwan. The final sample included 322 participants in the full sample which accounted for 58.42 % of the sample. A structural equation modeling (SEM) approach was used to evaluate the complex structure of the proposed research constructs. The study concluded that organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Innovative learning approach had no impact in the classroom for teachers to follow the practical guidelines in teaching, those teachers can design learning and guided discovery learning using guided discovery learning heuristic learning (Janssen, Westbrook, & van Driel, 2014), Implementation of discovery model of learning can increase students 'activity, increase understanding of the concept, and the students' critical thinking skills, as well as cognitive learning outcomes of students (Maulidar, Yusrizal, and Halim, 2016;Rosarina, Sudin, & Sujana, 2016). The teacher's role as a mediator and facilitator in learning connected with learning innovations that have a relationship between an organization's learning and organizational innovation (Hsiao et al, 2014),…”
Section: Discovery Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative learning approach had no impact in the classroom for teachers to follow the practical guidelines in teaching, those teachers can design learning and guided discovery learning using guided discovery learning heuristic learning (Janssen, Westbrook, & van Driel, 2014), Implementation of discovery model of learning can increase students 'activity, increase understanding of the concept, and the students' critical thinking skills, as well as cognitive learning outcomes of students (Maulidar, Yusrizal, and Halim, 2016;Rosarina, Sudin, & Sujana, 2016). The teacher's role as a mediator and facilitator in learning connected with learning innovations that have a relationship between an organization's learning and organizational innovation (Hsiao et al, 2014),…”
Section: Discovery Learningmentioning
confidence: 99%
“…Both professional teacher and pre-service teacher should understand and apply the approach to the learning process, academic content, pedagogical content, and evaluation/assessment, which is imbued with the essence of physics. Support and demand for innovation have a relation to the organization of learning and organizational innovation (Hsiao, Chang, & Chen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further research found that CSR has mediating effect towards consumer buying decision through consumer perception on corporate reputation [1]. This mediating effect of CSR was also supported by Chen [38]. Aside from corporate reputation, researcher argued CSR initiatives can enhance brand image which in the end improve corporate image [39].…”
Section: Literature Reviewmentioning
confidence: 95%
“…This condition describes a reflection of innovation success done by the researchers within the innovation ecosystem. It is also a reflection of the effectiveness of the reward and punishment system as well as innovation support [26].A literature study below identifies some variables which may contribute to the rise of innovation momentum: mood, mindset, thriving, creativity, government and organization supports. Mood and mindset comes from inside a researcher.…”
Section: Innovation Momentummentioning
confidence: 99%